Intelligent software methodologies, tools and techniques : 13th International Conference, SoMeT 2014, Langkawi, Malaysia, September 22-24, 2014. Revised selected papers /: 13th International Conference, SoMeT 2014, Langkawi, Malaysia, September 22-24, 2014. Revised selected papers. (2015) - Unknown
No abstract available